ASSESSING THE CHEMICAL PROPERTIES OF DAMMAR ASPHALT USING FOURIER TRANSFORM INFRARED SPECTROSCOPY - Ary Setyawan; M Fachri; A Sumarsono (UNIVERSITAS SEBELAS MARET (UNS), 2016)
Dammar Asphalt (Daspal) is expected to be used as a bio-asphalt renewable binder for road construction. It is made with a modification of the